2007
DOI: 10.1188/07.onf.127-132
|View full text |Cite
|
Sign up to set email alerts
|

Partner-Delivered Reflexology: Effects on Cancer Pain and Anxiety

Abstract: Hospitals could have qualified professionals offer reflexology as a complementary therapy and teach interested partners the modality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
134
1
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(142 citation statements)
references
References 26 publications
3
134
1
4
Order By: Relevance
“…For anxiety also 62 and 23% reduction in anxiety was reported for the treatment and control groups, respectively. Their findings indicated that reflexology can have a considerable role in mitigating pain and anxiety of patients [19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For anxiety also 62 and 23% reduction in anxiety was reported for the treatment and control groups, respectively. Their findings indicated that reflexology can have a considerable role in mitigating pain and anxiety of patients [19].…”
Section: Discussionmentioning
confidence: 99%
“…This is a promising outcome in using non-pharmacological nursing care that mitigates pain and anxiety for patients, especially in cancer patients. Most studies around the world suggest a positive effect of reflexology on anxiety and pain in patients suffering from different problems including different types of cancer [19,26,27,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aun así, los estudios basados en la evidencia no nos muestran un alto valor de que sean estadísticamente significativos 14 . Se han hecho estudios sobre TC y enfermos oncológicos en los que destacan los efectos positivos obtenidos, como la disminución del miedo [15][16][17][18][19] , de la ansiedad [15][16][17]19 , del dolor 20 , de los vómitos y náuseas producidos por la quimioterapia 21 , del estrés 18 y la fatiga [22][23][24] , así como el aumento de los sentimientos de control, relajación 25 , felicidad 26 , conciencia de sí mismo y autoestima 27,28 . De la misma forma, hay diversos estudios que concluyen que el paciente oncológico que se trata en el ámbito extrahospitalario (consultas privadas) pocas veces comenta a su médico oncólogo que es tratado con TC [12][13][14]29,30 .…”
Section: Introductionunclassified
“…8,9 Reflexology is often used as supportive care for cancer patients, especially for the reduction of pain, nausea and emotional disturbances, which include anxiety and depression. [10][11][12] Four previous reviews have assessed the value of reflexology. [13][14][15][16] However, these reviews are now outdated and focus on topics other than breast cancer.…”
Section: Introductionmentioning
confidence: 99%